The Relationship between Werner Syndrome and Sinonasal Malignant Melanoma: Two Sibling Cases of Werner Syndrome with Malignant Melanoma - Yoshinori Kadowaki; Satoru Kodama; Munehito Moriyama; Masashi Suzuki (Case Reports in Otolaryngology)
Werner syndrome (WS) is an autosomal recessive disease characterized by premature aging. Malignant tumors such as thyroid carcinoma and malignant melanoma occur frequently in WS patients. We describe 2 siblings with WS who suffered from sinonasal malignant melanoma (MM). Both patients initially experienced nasal obstruction and recurrent nasal bleeding and died within 2 years of the diagnosis of MM. Otolaryngologists should recognize that WS patients have a high risk for head and neck malignant disease, particularly sinonasal MM, even if they are aged below the expected age range and undergo periodic examinations. Furthermore, it is important that WS patients are aware that a prompt nasal examination is indicated if they experience continuous nasal obstruction or recurrent nasal bleeding.